Democratization Process and Youth Participation in Nigeria’s South East: A Post-Mortem on 2019 General Elections - ODUM, Mbanefo (Socialscientia: Journal of Social Sciences and Humanities, 2022)
The role of youths in the political process cannot be overemphasized. If properly utilized, their energy stands to make positive impact on the political system and this can be felt in the electoral and governance process through such means as participating actively in political campaigns, contesting for political offices, voting during elections, acting as electoral officers, holding political offices, making active inputs of demand/support on the political system, etc. If, on the other hand, they are not properly guided, their manner of participation can create catastrophic impact on the system. Indeed, the manner and extent to which the youths engage in these political activities differ from one political environment to another. Using the activities surrounding the Nigeria’s 2019 general elections, this study seeks to appraise the nature of political participation by the youths in the south eastern part of the country and its implication on the democratic process. The study is qualitative in nature and relies mainly on secondary sources for data gathering while relying on content analysis in analysing them. Findings reveal that the manner of political participation of the youths in the south eastern part of Nigeria leaves much to be desired and this is attributable to improper political socialization. The basic recommendation is that there is urgent need to engage the youths in political education and reorientation so as to guide them responsibly towards making meaningful political participation with a view to deepening the democratic values and culture.